Communication Methods in Addressing Religious Extremism: Ananalysis of the Munāṣaḥah of Wahb Ibn Munabbih - Murad, Azzahari; Ahmad, Aminudin Basir @ (Journal of Ecohumanism, 2024)
This study explores communication methods in addressing religious extremism through the munāṣaḥah of Wahb ibn Munabbih to an individual entangled in the Khawarij ideology. He was a prominent scholar among the Tabi'in, the first three generations of Muslims. His perspectives are crucial in the efforts to resolve religious extremism because of his communications methods which successfully brought the individual back to light. The study's methodology involves analysing the methods used by Wahb ibn Munabbih in his munāṣaḥah, utilizing primary and secondary data, and reviewing previous studies on communication methods in addressing religious extremism. The findings indicate that Wahb ibn Munabbih's communication approaches plays an important role in addressing religious extremism. This study concludes that the application of effective communication methods can significantly contributes to the efforts in combatting religious extremism and spread the accurate religious understanding and awareness in societies.